4‐Tert‐butylpyridine Free Organic Hole Transporting Materials for Stable and Efficient Planar Perovskite Solar Cells. Issue 19 (10th July 2017) - Xu, Bo; Zhu, Zonglong; Zhang, Jinbao; Liu, Hongbin; Chueh, Chu‐Chen; Li, Xiaosong; Jen, Alex K.‐Y.
Abstract: 4‐ Tert ‐butylpyridine ( t BP) is an important additive in triarylamine‐based organic hole‐transporting materials (HTMs) for improving the efficiency and steady‐state performance of perovskite solar cells (PVSCs). However, the low boiling point of t BP (196 °C) significantly affects the long‐term stability and device performance of PVSCs. Herein, the design and synthesis of a series of covalently linked Spiro[fluorene‐9, 9′‐xanthene] (SFX)‐based organic HTMs and pyridine derivatives to realize efficient and stable planar PVSCs are reported. One of the tailored HTMs, N2, N2, N7, N7‐tetrakis(4‐methoxyphenyl)‐3′, 6′‐bis(pyridin‐4‐ylmethoxy) spiro[fluorene‐9, 9′‐xanthene]‐2, 7‐diamine (XPP ) with two para‐position substituted pyridines that immobilized on the SFX core unit shows a high power conversion efficiency (PCE) of 17.2% in planar CH3 NH3 PbI3 ‐based PVSCs under 100 mW cm −2 AM 1.5G solar illumination, which is much higher than the efficiency of 5.5% that using the well‐known 2, 2′, 7, 7′‐tetrakis‐( N, N ‐di‐ p ‐methoxy‐phenyl‐amine)9, 9′‐spirobifluorene (Spiro‐OMeTAD) as HTM (without t BP) under the same condition. Most importantly, the pyridine‐functionalized HTM‐based PVSCs without t BP as additive show much better long‐term stability than that of the state‐of‐the‐art HTM Spiro‐OMeTAD‐based solar cells that containing t BP as additive. This is the first case that the t BP‐free HTMs are demonstrated in PVSCs with high PCEs and good stability. It paves the way to develop highly efficient and stable t BP‐free HTMs for PVSCs toward commercial applications. Abstract : A series of covalently linked organic hole‐transporting materials (HTMs) and pyridine derivatives are developed for 4‐ tert ‐butylpyridine ( t BP) free planar perovskite solar cells (PVSCs). One of the HTM‐N2, N2, N7, N7‐tetrakis(4‐methoxyphenyl)‐3′, 6′‐bis(pyridin‐4‐ylmethoxy) spiro[fluorene‐9, 9′‐xanthene]‐2, 7‐diamine (termedXPP ) shows a remarkable power conversion efficiency of 19.5% and excellent long‐term stability in mix‐ion planar PVSCs without t BP as additive.